2011 Global Food Policy Report - Fan, Shenggen (2012)
Presentation delivered by IFPRI Director General Shenggen Fan on April 23, 2012 for the launch of the 2011 Global Food Policy Report at IFPRI's Headquarters in Washington, DC.